Somatostatin Receptors in Merkel-Cell Carcinoma: A Therapeutic Opportunity Using Somatostatin Analog Alone or in Association With Checkpoint Inhibitors Immunotherapy. A Case Report - Guida, Michele; D'Alò, Alessandro; Mangia, Anita; Di Pinto, Federica; Sonnessa, Margherita; Albano, Anna; Sciacovelli, Angela; Asabella, Artor Niccoli; Fucci, Livia (Frontiers in Oncology, 2020)
Background: Merkel-cell carcinoma (MCC) is a rare aggressive skin cancer typically involving elderly people. Surgery is usually the first treatment for primary tumor. Also adjuvant radiotherapy has been shown to be effective in reducing the rates of local recurrence and increasing overall survival. In the advanced disease, systemic chemotherapy was used with disappointing results. Recently, antiPD1/antiPD-L1 immunotherapy have given much more clinical benefits. Interestingly, about the half of MCC patients expresses highly somatostatin receptors (SRs) that could represent a rationale for the therapeutic use of somatostatin analogs (SSAs) alone or in association with immunotherapy. However, so far SSAs have been poorly studied in MCC and cases treated with SSAs in association with checkpoint inhibitor immunotherapy have not yet been published. Case report: We report the case of a 73-year-old man affected by metastatic MCC of right arm previous treated with surgery and adjuvant radio-chemotherapy. Three years later patient presented loco-regional relapse involving latero-cervical, mediastinal, and submandibular lymph nodes with high value of Chromogranin A (CgA) and Neuron Specific Enolase (NSE). Due to the high expression of SRs at octreoscan and immunoistochemistry, patient started octreotide 30 mg i.m. every 28 days with a good control of disease for about 2 years. Successively, he presented a widespread progression of the disease. Considering the recent availability in Italy of the antiPD-L1 avelumab immunotherapy, the patient initiated this drug continuing SSA. After only 4 cycles of intravenously avelumab, the patient showed an impressive regression of the disease until complete remission. Conclusions: SSA could represent a valid therapeutic option in patients with MCC with high SR expression. When combined with anti PD1/anti PD-L1 immunotherapy, SSA could enhance antiproliferative activity. For this purpose, prospective studies are strongly to be encouraged.